Random Vibration of Space Shuttle Weather Protection Systems - Isaac Elishakoff; Menahem Baruch; Liping Zhu; Raoul Caimi (Shock and Vibration)
The article deals with random vibrations of the space shuttle weather protection systems. The excitation model represents a fit to the measured experimental data. The cross-spectral density is given as a convex combination of three exponential functions. It is shown that for the type of loading considered, the Bernoulli-Euler theory cannot be used as a simplified approach, and the structure will be more properly modeled as a Timoshenko beam. Use of the simple Bernoulli-Euler theory may result in an error of about 50% in determining the mean-square value of the bending moment in the weather protection system.